Strengthening of axially loaded circular concrete columns using stainless steel wire mesh (SSWM) – Experimental investigations. (15th October 2016) - Kumar, Varinder; Patel, P.V.
Highlights: The SSWM, a locally available material can be used for axial strengthening of circular concrete columns. The increase in strength with SSWM wrapping decreases with increase in concrete grade from M15 to M25. The increase in strength is higher in case of longer columns. The columns damaged due to corrosion can be strengthened with SSWM without increasing size. SSWM is much economical than CFRP OR GFRP meshes. Abstract: An experimental investigation is presented in this paper for evaluation of axial strength of M15, M20, and M25 grade plain cement concrete (PCC) circular columns strengthened with locally available stainless steel wire mesh (SSWM). Column specimens of 200 mm diameter with various heights 400 mm, 800 mm and 1200 mm are used in the study. Specimens are strengthened with one and two wraps of SSWM and their performance under axial load is compared with control specimens. Ultimate tensile strength of SSWM and bond strength of SSWM with concrete are studied to check the feasibility of SSWM for strengthening. From study of 54 columns specimens, it is found that axial compressive strength is increased up to 61% and 86% when columns are strengthened with one and two wraps of SSWM respectively. Axial load carrying capacity of columns obtained from experimental study is compared with that specified by ACI 440.2R-08 and CNR DT 200/2004. It is observed that experimental results closely match with specification CNR DT 200/2004. Based on present study, it is concluded that SSWM can be used for strengthening of concrete columns economically as compared to carbon fiber or glass fiber polymer.